2018
DOI: 10.24879/2018001200300506
|View full text |Cite
|
Sign up to set email alerts
|

Ideação suicida em assentamentos rurais no Piauí

Abstract: Objetiva investigar casos de ideação suicida em áreas de assentamentos rurais no Piauí. Para isso, realizou-se estudo de corte transversal em dois assentamentos rurais. Por meio de questionário sócio demográfico e o instrumento Self-Reporting Questionnaire (SRQ-20), identificou-se casos de transtorno mental comum na população investigada, com destaque para indivíduos que pontuaram o item do questionário que trata da presença de pensamentos suicidas. Para análise dos dados utilizou-se o pacote estatístico SPSS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Living and working conditions in the countryside can hide the harsh reality of the situations of poverty, unemployment, precarious access to health and education, and also situations of exploitation, violence, fear, insecurity, and the presence of common mental disorders, constituting some risk factors for suicidal behavior in rural populations, especially in farmers [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Living and working conditions in the countryside can hide the harsh reality of the situations of poverty, unemployment, precarious access to health and education, and also situations of exploitation, violence, fear, insecurity, and the presence of common mental disorders, constituting some risk factors for suicidal behavior in rural populations, especially in farmers [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigação conduzida em comunidades quilombolas e assentamentos rurais também observaram uma maior prevalência de sofrimento psíquico entre as mulheres 4,22 . Essa distribuição desigual de sintomas de TMC entre os sexos pode ser compreendida, dentre outros fatores, pela elevada carga de trabalho, tanto no seio familiar quanto na comunidade, associada com a desvalorização e invisibilidade do trabalho feminino, gerando uma grande sobrecarga física e emocional 4,22,23 . Destaca-se ainda que os papéis femininos tradicionais -como esposa, mãe, filha e cuidadora -aliados aos fatores sociais que abrangem desemprego, situação de violência e condições precárias de vida e saúde, contribuem para o adoecimento psíquico das mulheres 11 .…”
Section: Resultsunclassified
“…To calculate the sample size for finite populations, the prevalence of suicidal ideation in rural populations of 13% was considered [ 12 ]. Considering the absolute error margin of 3%, 15% non-response rate, estimated proportion of the event of 13% and the finite population of 2000 farmers, the calculated sample corresponded to 450 farmers.…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, however, there are few studies presenting robust data on suicidal ideation among farmers. A study with a rural population identified a prevalence of suicidal ideation of 13.4% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation